2000
DOI: 10.1067/mva.2000.107991
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-induced changes in lower extremity superficial veins: An ultrasound scan study

Abstract: The diameters of competent and incompetent superficial veins increased during pregnancy and decreased during the postpartum period to return to their baseline values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 17 publications
1
25
0
3
Order By: Relevance
“…Chronic venous disease (CVD) refers to various anomalies commonly affecting the lower extremities, in which venous return is abnormal, and varicose veins are the most important clinical manifestation [1]. Pregnancy is associated with an increased risk of developing chronic venous disorder [2,3]. Risk factors associated with venous disorder during pregnancy include genetic factors and family history, occupation, and the number of pregnancies or the interval between pregnancies [4].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic venous disease (CVD) refers to various anomalies commonly affecting the lower extremities, in which venous return is abnormal, and varicose veins are the most important clinical manifestation [1]. Pregnancy is associated with an increased risk of developing chronic venous disorder [2,3]. Risk factors associated with venous disorder during pregnancy include genetic factors and family history, occupation, and the number of pregnancies or the interval between pregnancies [4].…”
Section: Introductionmentioning
confidence: 99%
“…17 Also, Sparey et al found that normal veins, in spite of changes in venous diameter during pregnancy comparable with that seen in those with pre-existing venous disease, return to normal after delivery, but some VVs deteriorate during pregnancy, and this may be progressive with successive pregnancies. 18 Previously, Cornu-Thenard et al had already observed a correlation between the total number of pregnancies and the size of VVs.…”
Section: Risk Factors and Concurrent Diseasesmentioning
confidence: 99%
“…31 Some authors have defined as non-saphenous reflux those VVs that are not part of GSV or SSV systems. 17,32 Therefore, they include reflux from perineal and PV systems. From our point of view, they should differentiate.…”
Section: Reflux Pattern According To the Venous Reflux Pointmentioning
confidence: 99%
“…This may be attributed to hormonal variation from the onset of menses until menopause and during pregnancy. [15][16][17][18][19][20] The prevalence of reflux in SN and TN among all the limbs studied was 1% (9/835) and of the limbs with nonsaphenous vein reflux 10.7% (9/84).…”
Section: Discussionmentioning
confidence: 98%